PENGARUH VARIASI FUEL CORRECTION TERHADAP KONSUMSI BAHAN BAKAR PADA MOBIL TARSIUS GV-2 UNIVERSITAS BANGKA BELITUNG - budi santoso wibowo; suhdi suhdi; Saparin Saparin; Yudi Setiawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2022)
The Energy Efficient Car Competition (KMHE) is an annual competition organized by the national achievement center (puspernas), Bangka Belitung University regularly participates in the KMHE competition starting from 2015 to 2022, but UBB's KMHE car has not been able to compete to win the category of prototype gasoline, car KMHE has many shortcomings, especially fuel consumption which is still relatively high, namely 130 km / liter, one method of saving fuel consumption is by adjusting the length of time the injector opens (fuel correction). This study aims to determine the effect of the fuel correction value with a variation of 0 , -11, -23, and -27 on fuel consumption. The Electronic Control Unit (ECU) used is a programmable type ECU, the test is carried out at various engine speeds (RPM 1000, 2000, 3000, 4000 and 5000) with a 5 minute test time. The results showed that the most efficient data on fuel consumption was at fuel correction -27 at 1000 RPM, namely 4 ml and the highest fuel consumption was at correction 0 at 5000 rpm, which was 67 ml.